Evaluasi Program Pengendalian Lumpur Sidoarjo Melalui 4P (Pengaliran, Peralatan, Perkuatan, dan Penataan) di Pusat Pengendalian Lumpur Sidoarjo - Inayatullah, Septia Intan; Prabawati, Indah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The mud control program through the 4P (Flow, Equipment, Reinforcement, and Arrangement) is a program formed as an effort to overcome mud bursts in Sidoarjo. The Sidoarjo Mud Control Center under the Ministry of Public Works was appointed to carry out tasks related to the control of mud bursts in Sidoarjo. In its implementation, PPLS refers to the Strategic Plan for 2020 – 2024. The research method used is a descriptive method with a qualitative approach. The study used six indicators of program evaluation by William Dunn. The results of the study show that PPLS's efforts in realizing effectiveness in program implementation are measured through the achievement of activity targets and Activity Performance Indicators (IKK). Efficiency is in the form of determining the priority of activities, the use of existing equipment and the placement of human resources based on competencies. Equitable distribution of the community who receives compensation for the affected land and buildings. Adequacy in maximizing the use of 15-year-old program support equipment. Responsiveness by conducting Focus Group Discussions (FGD) and community empowerment through training on making bricks from mud materials. Accuracy in the implementation of work through a series of calculations, analyses and studies. Efforts to improve the results of the evaluation can be done by utilizing Corporate Social Responsibility (CSR) to open up opportunities for supporting equipment and improving the quality and frequency of technical training for human resources, as well as strengthening digital-based monitoring and evaluation systems through innovative cooperation with the private sector and start-ups in the technology sector, as well as consulting with legal experts in assisting in the fulfillment of submission documents budget to avoid budget.